Diffusion-Controlled Growth of Oxygen Bubble Evolved from Nanorod-Array TiO2 Photoelectrode - Xiaowei Hu; Yechun Wang; Liejin Guo; Zhenshan Cao (Advances in Condensed Matter Physics)
Nanorod-array structure gains its popularity in photoelectrode design for water splitting. However, the structure’s effects on solid-liquid interface interaction and reaction product transportation still remain unsolved. Gas bubble generally evolved from photoelectrodes, which provides a starting point for the problem-solving. Based on this, investigations on the gas-evolving photoelectrode are carried out in this paper. By experimental studies of wettability on the photoelectrode nanorod-array surface and oxygen bubble growth from anode, we analyzed the interaction affecting the gas-solid-liquid contact behaviors and product transportation mechanism, which is controlled by diffusion due to the concentration gradient of dissolved gases in the aqueous electrolyte and the microconvection caused by the bubble interface movement. In the end, based on the bubble growth characteristics of RB(t)~t0.5 in the experiment, a model describing the product transport mechanism was presented.